Management of Aphakia with Visual Axis Opacification after Congenital Cataract Surgery Based on UBM Image Features Analysis - Wensi Chen; Shiping He; Daoman Xiang (Journal of Ophthalmology)
Objective. The purpose of this study was to study the imaging features of ultrasound biomicroscopy (UBM) in the aphakia with visual axis opacification (VAO) after congenital cataract surgery. Methods. From May 2015 to May 2018, aphakia patients with VAO who underwent congenital cataract surgery were examined by high-resolution bag/balloon UBM technique, and the results of UBM imaging were analyzed. According to UBM imaging features, different types of VAO were classified. Results. A total of 38 children (55 eyes) with VAO were included. 17 patients were bilateral, and 21 patients were unilateral. Patients with VAO were classified into 3 groups according to the UBM imaging features: membranous fibrosis VOA (17 cases, 28 eyes), cortical regeneration VOA (15 cases, 20 eyes), and mixed VOA (6 cases, 7 eyes). The patients in the membranous fibrosis group underwent Nd:YAG laser posterior capsulotomy, those in the cortical regeneration group underwent anterior vitrectomy, and those in the mixed type group underwent anterior vitrectomy with RF capsulotomy tip. After surgery, VAO were removed in all patients. During the follow-up period, in the membranous fibrotic VAO group, iris adhesion and pupillary occlusion were found in 2 eyes, and anterior vitrectomy combined with separation of iris adhesion was performed. In cortical regenerative and mixed type VAO groups, anterior vitrectomy was performed without opacity in the axial region. The total recurrence rate of VAO was 3.46%. Conclusion. After congenital cataract surgery, the UBM imaging features of aphakia with VAO are helpful to evaluate the condition of VAO before reoperation so as to choose the optimal surgical method to achieve better therapeutic effect.